2012
DOI: 10.2478/s11535-012-0044-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute heat stress on rat adrenal medulla — a morphological and ultrastructural study

Abstract: Isolated rat adrenal medulla was analyzed by light and electron microscope after an acute (60 min) exposure to high ambient temperature (38°C). Under these conditions there was a significant rise in plasma adrenaline and noradrenaline. Stereological investigation by light microscopy showed a significant decrease in volume density of cells and an increase in the interstitium. At the ultrastructural level, the profile area of cells, nuclei and cytoplasm of adrenaline cells were significantly decreased. After the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(44 reference statements)
1
1
0
Order By: Relevance
“…Such a degranulation of chromaffin cells has been also observed in rat after various stressors [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Also, signs of cell degeneration were evidenced in chromaffin cells displayed by hypertrophy of cells with loss of cell borders, vacuolation of cytoplasm, and pyknotic nuclei.…”
Section: Discussionsupporting
confidence: 53%
“…Such a degranulation of chromaffin cells has been also observed in rat after various stressors [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Also, signs of cell degeneration were evidenced in chromaffin cells displayed by hypertrophy of cells with loss of cell borders, vacuolation of cytoplasm, and pyknotic nuclei.…”
Section: Discussionsupporting
confidence: 53%
“…Nevertheless, the noradrenaline content of the brain was significantly increased in 30 and 50 mg/kg body weight groups compared with other groups during summer season. Heat exposure led to increase concentrations of plasma and changes in the cells of adrenal gland medulla in the rats (Petrovic-Kosanovic et al, 2012). Also, Yuan et al (1989) found that heat exposure for 15 min at 45°C reduced the brain content of noradrenaline (NA) in mice.…”
Section: Neurotransmittersmentioning
confidence: 99%